2021
DOI: 10.26508/lsa.202000849
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of inhibitor-bound human MSPL that can activate high pathogenic avian influenza

Abstract: Infection of certain influenza viruses is triggered when its HA is cleaved by host cell proteases such as proprotein convertases and type II transmembrane serine proteases (TTSP). HA with a monobasic motif is cleaved by trypsin-like proteases, including TMPRSS2 and HAT, whereas the multibasic motif found in high pathogenicity avian influenza HA is cleaved by furin, PC5/6, or MSPL. MSPL belongs to the TMPRSS family and preferentially cleaves [R/K]-K-K-R↓ sequences. Here, we solved the crystal structure of the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…In our 3-D protein modeling, modules in the TMPRSS2 extracellular region appeared to fold independently. The results are consistent with recently published structures of a partial TMPRSS2 extracellular fragment without the LDLR domain ( 60 ) and the full-length extracellular region of TMPRSS13 ( 76 ). N286 is located between the SRCR and the protease domains.…”
Section: Discussionsupporting
confidence: 92%
“…In our 3-D protein modeling, modules in the TMPRSS2 extracellular region appeared to fold independently. The results are consistent with recently published structures of a partial TMPRSS2 extracellular fragment without the LDLR domain ( 60 ) and the full-length extracellular region of TMPRSS13 ( 76 ). N286 is located between the SRCR and the protease domains.…”
Section: Discussionsupporting
confidence: 92%
“…To test this hypothesis, we investigated the impact of S813T mutation on the S2’ site cleavage on VSVpp and S proteins by TPCK-trypsin, the serine protease domain of which has extremely high homology with TMPRSS2 [ 52 ] and previous studies have used it to observe the S2’ formation [ 53 , 54 ]. WB analyses showed that S813T mutation had the most significant effect on S2’ cleavage compared with other point mutations in IFP ( Fig 6B left).…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, the S1 site is formed without alteration of the catalytic triad. Of note, the conformation of loops 1 and 2 in TMPRSS2 S441A -Cl is the same those of active forms of hepsin 33 and TMPRSS13 (also called MSPL) 34 (Figure SI4C).…”
Section: Resultsmentioning
confidence: 69%
“…Of note, the conformation of loops 1 and 2 in TMPRSS2 S441A -Cl is the same those of active forms of hepsin 33 and TMPRSS13 (also called MSPL) 34 (Figure SI4C).…”
Section: Nanobody A07 Inserts Its Cdr3 Into the Tmprss2 Substrate-bin...mentioning
confidence: 69%